AN ANALYSIS OF ACADEMIC READING DIFFICULTIES ENCOUNTERED BY THE SECOND YEAR STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Novianti, Reni; Erni, Erni; Azhar, Fadly (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: Academic reading is one of the challenges commonly faced byuniversity students. This quantitative descriptive research aimed to know the aspects of academic reading difficulties and the factors that cause the problems faced by the second-year students of the English study program FKIP Universitas Riau. The population was 111 students. A random sampling technique was applied to decide the sample. There were 38 students as the samples. The instrument used to collect the data was a reading test categorized into 7 components about the aspects of the student's academic reading difficulties faced and a questionnaire with categorized 3 aspects of the factors that cause academic reading difficulties. To analyze the data, the researcher calculated the data using Microsoft Excel 2013. The data analysis showed that the mean score was 50.59 categorized into medium level. The findings of the research showed that the highest aspects of academic reading difficulties faced by the students were in answering questions about identifying inference with 22 students (58%) and the factors that caused academic reading difficulties faced by the students such as lack of language proficiency (57%), limited of background knowledge (58%), and Inadequate use of effective reading strategies (63%). Hence, students are suggested to be more practiced in learning and reading academic texts to understand better how to overcome their problems by developing their reading skills by applying various reading strategies and encouraging their reading habits in learning academic texts.Key Words: Analysis, Academic Reading, Difficulties